PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATKAN MOTIVASI PESERTA DIDIK PADA PEMBELAJARAN IPAS TINGKAT SD - Atfaliyah, Khodikotul; Suganda, Ahmad; Yulianti, Hani; Hanifatunnufus, Fera; Lia, Alma; Imroatussolihah, Imroatussolihah (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
The use of effective learning media can improve the quality of learning and help students achieve learning goals. This study aims to determine the use of game-based learning media wordwall can improve student motivation in science learning in elementary school. This study uses a descriptive qualitative method. This research was conducted at UPT SDN Blok I Cilegon. The subjects of the study were grade III students. Data collection techniques used include: observation, interviews, and documentation. The results of this study indicate that students are more enthusiastic and more motivated in the application of Wordwall learning media. Students are also more active during the learning process and they do not feel bored even though the traditional method is still used when providing material